2014
DOI: 10.1074/jbc.m114.573238
|View full text |Cite
|
Sign up to set email alerts
|

N-Glycosylation of Asparagine 8 Regulates Surface Expression of Major Histocompatibility Complex Class I Chain-related Protein A (MICA) Alleles Dependent on Threonine 24

Abstract: Background:Immune activation through surface expression of the human NKG2D ligand MICA is important in clearance of virus-infected or cancerous cells. Results: Molecular characterization of N-glycosylation in regulation of MICA cell surface expression. Conclusion: Surface expression of MICA alleles vary in dependence for N-glycosylation. Significance: We identify N-glycosylation as an allele-specific regulatory mechanism of MICA and pinpoint the essential residues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 58 publications
1
19
1
1
Order By: Relevance
“…However, the mechanisms behind ULBP4 translocation remain elusive. Some studies have demonstrated that N-linked glycosylation regulated the translocation of MICA/B from the cytoplasm to the membrane (57,58). However, we have shown that tunicamycin, a selective inhibitor of N-linked glycosylation, did not abolish HCQ-induced ULBP4 expression (data not shown).…”
Section: Discussioncontrasting
confidence: 60%
“…However, the mechanisms behind ULBP4 translocation remain elusive. Some studies have demonstrated that N-linked glycosylation regulated the translocation of MICA/B from the cytoplasm to the membrane (57,58). However, we have shown that tunicamycin, a selective inhibitor of N-linked glycosylation, did not abolish HCQ-induced ULBP4 expression (data not shown).…”
Section: Discussioncontrasting
confidence: 60%
“…Indeed, it is wellestablished that certain MICA alleles/amino acids affect its binding affinity for NKG2D (for review, see Carapito and Bahram 18 ; for an example, see Mellergaard et al 41 ). Furthermore, and in accordance with a rather restricted expression pattern for the MICA glycoprotein, it is perhaps not surprising that MICA mismatches are associated with limited (and not extensive; ie, multiorgan) chronic GVHD (supplemental Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, MICA*A5.1 carriers may have an aberrant immunological surveillance by NK and T cells [9,52]. Furthermore, N-glycosylation requirement for cell trafficking of MICA*A5.1 is also different: there is an alanine residue at position 24 (a1 domain) in MICA*A5.1, instead of threonine; Thr 24 N-glycosylation directly regulates MICA surface expression and, therefore, regulation of the expression of MICA*A5.1 allele is not affected by changes in N-glycosylation [53]. MICA*A5.1 is not released from cells by proteolytic shedding due to the lack of the two cysteines required, but rather as a membrane anchored full-length molecule in exosomes [50,54].…”
Section: Discussionmentioning
confidence: 99%